2017
DOI: 10.1080/09638237.2017.1322186
|View full text |Cite
|
Sign up to set email alerts
|

The impact of coping and emotional intelligence on the relationship between posttraumatic stress disorder from past trauma, adjustment difficulty, and psychological distress following divorce

Abstract: Following divorce, people can experience psychological distress which is influenced by the effects of PTSD from past trauma, and whether they used problem-focused coping and were able to manage their emotions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 70 publications
1
3
0
Order By: Relevance
“…Our results confirmed previous findings showing that pre-displacement stressors are associated with PTSD symptoms and psychological distress among the displaced population [13,9]. Similar to the outcomes of previous works [14][15][16], our results showed a significant and positive relationship between psychological distress and PTSD symptoms. Results further suggested that longer duration in camp and being single predicted higher levels of PTSD symptoms severity and psychological distress.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results confirmed previous findings showing that pre-displacement stressors are associated with PTSD symptoms and psychological distress among the displaced population [13,9]. Similar to the outcomes of previous works [14][15][16], our results showed a significant and positive relationship between psychological distress and PTSD symptoms. Results further suggested that longer duration in camp and being single predicted higher levels of PTSD symptoms severity and psychological distress.…”
Section: Discussionsupporting
confidence: 92%
“…Although studies have examined the impact of pre-displacement stressors on psychological distress and PTSD symptoms, there is a need to understand how these stressors impact the reciprocal relationship between psychological distress and PTSD symptoms. It has been demonstrated that greater PSTD levels may predict increased psychological distress [14][15][16], and a history of psychological distress may predict increased PTSD [17,18]. Research has also shown that PTSD is usually comorbid with psychological distress [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Based on research evidence, Leopold (2018) concluded men were more vulnerable to short-term consequences of divorce, while in the mid-term both men and women's adjustment to divorce was similar, but more significantly men's strain of divorce in the longterm was transient while for women it was chronic. According to Slanbekova1 et al (2017), divorced women show poor social and family adjustments and are more depressed, lonely and financially burdened.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research shows that EI capacities and coping styles are of utmost importance in family divorce when building mutual parenting is complicated and full of personal and interpersonal challenges (8,9). Individuals affected by parental divorce have a higher risk of developing a variety of mental health conditions, and psychosomatic and psychosocial disorders.…”
mentioning
confidence: 99%